Habitual Residence And Its Role In Matters Of The Nationality (Journal of Namibian Studies : History Politics Culture, 2023)
The habitual residence is one of the most important standards in private international law, as it has been used in several fields at the national and international levels, as it replaced the domicile and nationality, being more flexible and open to the needs of individuals, until it became a key attribution officer to determine international jurisdiction and determine the applicable law in many national legislation and international conventions.